Case for using locally grown food on campus - Townsend, Justin (My University, 2008)
As The University of Wisconsin River Falls has made the decision to be at the forefront of sustainable community development in the region, it becomes very important to look at all aspects of campus. Since our current food service contractor uses unsustainable practices, I researched the possibilities and benefits of using our local food stocks. My research was primarily looking at hidden costs of the food we eat here on campus based on previous research done by ecologists and economists. I also studied the feasibility of using our local food stock by using other universities, local programs, and our current use of local products. What I discovered was two important facts about our food services on campus. First, it was not sustainable and promoted a system that harmed our local economy, our neighbors, and the environment around the globe. Secondly, I found if we made a few changes in procurement our food services could provide a higher degree of freshness and nutrition to River Falls' students and staff. The conclusion I came to is that UW-River Falls should support imposed guidelines that tell our food service how much they must spend in our community.
Color poster with text describing research conducted by Justin Townsend, advised by Dr. Kelly Cain (University of Wisconsin-River Falls) on the idea of using locally grown food on the campus of the University of Wisconsin-River Falls.
Keywords: Farm-to-college; Food service; Locally grown food; Food--Environmental aspects; Sustainable development; University of Wisconsin-River Falls; St. Croix Institute for Sustainable Community Development; Food industry and trade; University of Wisconsin-River Falls food service; Food supply; Local food; Sustainability